OP0077-HPR The effect of an interactive workshop on the adherence with the dutch physical therapy practice guideline for hip and knee osteoarthritis: A randomised controlled trial. (23rd January 2014) - Peter, W.F.; van der Wees, P.H.; Verhoef, J.; de Jong, Z.; van Bodegom-Vos, L.; Hilberdink, W.K.; Fiocco, M.; VlietVlieland, T.P.
Abstract : Background: Literature (1) and daily practice indicate a need for interactive forms of education to enhance guideline usage, but the evidence on their effectiveness is lacking. Objectives: The aim of this study was to investigate the effectiveness of an interactive workshop as part of the implementation of the Dutch physical therapy (PT) guideline for hip and knee osteoarthritis (HKOA). Methods: In 5 regions in the Netherlands, all PTs who were a member of the Royal Dutch Society of Physical Therapy were randomly assigned to an interactive workshop (IW) or a control group (C). IW comprised presentations of the content of the guideline and 3 clinical cases with the cooperation of 3 patient partners and 3 expert PTs per region, executed according to the method of clinical reasoning and lasted 3 hours. C was a waiting list group who received IW after 4 months. Assessments were done before the educational course, immediately afterwards and three months thereafter. Assessments consisted of the Quality Indicators for Physical therapy in Hip and Knee Osteoarthritis (QIP-HKOA) questionnaire, containing 18 questions on the usage of the guideline (total score range 0-72), a 19-items knowledge questionnaire (total score range 0-76) and a questionnaire concerning barriers in using the guideline (total score range 0-80). In addition, sociodemographic characteristics of the participants were recorded. Statistical analysis included comparisons of total mean scores between the IW and C across 3 time points by using Linear Mixed Models. Results: In total 3778 PTs were invited, of whom 275 (7.3%) were willing to take part in the study. They were randomly assigned to IW (n=141) or C (n=134). There were no sociodemografic differences at baseline between IW and C. The statistic analyses showed a significant difference between groups in favour of IW concerning all 3 outcome measures (see Table 1). Conclusions: An interactive educational course with the support of patients and following a process of clinical reasoning was found to be an effective strategy to improve adherence with recommendations in the Dutch physical therapy guideline for HKOA. Also knowledge about the guideline improved and less barriers to use the guideline were experienced in daily clinical practice after 3 months. Funding: This project was funded by the Royal Dutch Society of Physical Therapy and the Dutch Arthritis Association. References: Lineker SC et al. Educational Interventions for Implementation of Arthritis Clinical Practice Guidelines in Primary Care: Effects on Health Professional Behavior, the Journal of Rheumatology 2010; 37:8. Disclosure of Interest: None Declared